14th annual Congress of the European College of Sport Science - ECSS 2009 - Oslo 24.-27.6.2009 - Book of abstracts (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Sport is a complex phenomenon that includes most dimensions of human life. The complete study of human activity in sport must build on a diversity of scientific approaches. The 14th Annual Congress programme feature theoretical, applied and cross-diosciplinary sport studies as well as research findings based on the natural, behavioural, social and human scientific disciplines. The scientific programme is composed of more than 1.400 abstracts which were accepted after careful review by the scientific committee of the ECSS and the local scientific committee of the NSSS. The strong interest in this Congress underlines the growth and increasing significance of the ECSS as an interdisciplinary forum for ongoing debate. The presented abstracts comprise not only all relevant sport science subdisciplines and themes but also all continents and 79 different nations. The abstracts are distributed among four Plenary Sessions, 36 Invited Symposia, 74 Oral Sessions, and four Poster Sessions with more than 870 posters.